The anatomy of hügelkultur and dissecting the key claims - Hazan, Sara (My University, 2025)
Hügelkultur, German for “hill culture”, was first defined in 1962 and adopted by the permaculture community in the subsequent decades. The technique typically involves layering woody organic matter with soil and compost, or other available organic matter, to create a raised bed—which is then planted on all sides. Practitioners claim that the principles upon which hügelkultur function is grounded in science. However, no controlled, replicated research on inherent hügel bed characteristics or performance has been identified in the literature. This review seeks to ground the more prominent claims about hügelkultur by reviewing similar topics in published scientific literature. Hügelkultur proponents claim that, among other things, hügel beds reduce irrigation and fertility requirements, increase soil organic matter content, sequester carbon, and provide a beneficial microclimate for crop production. However, others point out that irrigation and rainfall may lead to runoff and erosion from the relatively steep slopes of the hügel beds; and, as the woody organic skeleton underlying hügelkultur breaks down, settling may harm established plant roots. While some of these claims may have merit based on the current understanding of plant and soil ecology, remain unvalidated in the specific context of hügelkultur. Where commercial applications could apply—e.g. distinct microclimates may have implications for season extension in annual specialty crops—further research is warranted. This review examines common claims found in anecdotal accounts and grey literature against relevant peer-reviewed literature, from related disciplines, to assess their potential validity and propose possible avenues for hügelkultur research.
Keywords: Hügelkultur; Permaculture; Microclimate; Soil health; Literature review